IMPROVING VOCABULARY AND TAHAJJUD HABIT USING CHAIN SMS IN TAHAJJUD TIME FOR THE FIFTH GRADE STUDENTS OF MI AL MUBAROK WANGKAL SIDOARJO - Muflikh Wakhidi; Rakhmawati Rakhmawati; Ana Nurul Laila (IJET (Indonesian Journal of English Teaching), 2016)
Vocabulary is an important aspect in the process of learning English because it is needed by the students when they are learning English language skills. Therefore, teaching English in primary schools are held to provide students a larger amount of vocabulary than what they probably have before. This research is designed to improve the students’ vocabulary as well as their Tahajjud (night prayer) habit using Chain SMS sent during Tahajjud time. The method was selected because it was believed to be able overcome the problem of limited time at school and allow students to memorize vocabulary gradually since they will learn after they have enough rest and after they did they tahajjud prayer. This is a a Classroom Action Research (CAR) designed in two cycles. The subjects of this research were 29 students of the fifth grade of MI Al Mubarok Wangkal in the 2014/2015 academic year. The data of this research study were obtained through vocabulary test documentation. The findings of this research indicated that the Chain SMS in Tahajjud time was successful in improving both the students’ ability in vocabulary and the students’ Tahajjud habit. The improvement can be seen from the increase of students’ scores and the students’ individual score percentage from preliminary study to Cycle 2 both for vocabulary achievement and Tahajjud prayer habit.